Genomic analysis of DS-1-like human rotavirus A strains uncovers genetic relatedness of NSP4 gene with animal strains in Manhiça District, Southern Mozambique - Manjate, Filomena (2024)
0.870\u2009\u2212\u200915 SC; The United States Agency for International Development (USAID), grant number AID-656-F-16-00002 and Fundo Nacional de Investiga\u00E7\u00E3o (FNI), Mo\u00E7ambique, grant number 245-INV funded the implementation of the surveillance of rotavirus and other enteropathogens in children less than 5 years of age in Manhi\u00E7a. The whole genome characterization undertaken in this study was supported by The Child Health and Mortality Prevention program (Surveillance), CHAMPS funded by the Bill & Melinda Gates Foundation under Grant OPP1126780; The Funda\u00E7\u00E3o para a Ci\u00EAncia e a Tecnologia for funds to GHTM-UID/04413/2020 and LA-REAL \u2013 LA/P/0117/2020, Instituto de Higiene e Medicina Tropical (IHMT), Universidade Nova de Lisboa, Portugal and the Next Generation Sequencing Unit, and the Division of Virology, Faculty of Health Sciences, University of the Free State, South Africa. The Calouste Gulbenkian Foundation financed F. M\u2019s PhD studies, under the grant number 234066. CISM receives core funding from the Mozambican government and the \u201CAgencia Espa\u00F1ola de Cooperacion Internacional para el Desarollo (AECID).\u201D Publisher Copyright: © The Author(s) 2024.